2012
DOI: 10.5539/gjhs.v5n1p28
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Implications of the Use and Misuse of Tobacco among the Aboriginals in Canada

Abstract: Tobacco smoking among the Aboriginal populations is a major public health issue in Canada. It remains a major contributory risk factor to the poor health status as well as years of potential life lost seen among the indigenous people. The use of tobacco has a spiritual importance to the people as a means of making connection to the Creator, but unfortunately tobacco smoking has taken a recreational aspect which has little or no connection with Aboriginal spirituality. The non-traditional use of tobacco is beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
0
15
0
5
Order By: Relevance
“…Native/Aboriginal students, because of their cultural background, are more likely to adhere to a holistic approach that encompasses the spiritual, mental, physical, and emotional aspects of health [38]. This might explain why the use of NHP, especially medicinal plants, is appealing to Native/Aboriginal students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native/Aboriginal students, because of their cultural background, are more likely to adhere to a holistic approach that encompasses the spiritual, mental, physical, and emotional aspects of health [38]. This might explain why the use of NHP, especially medicinal plants, is appealing to Native/Aboriginal students.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to more questions about commercial tobacco use and misuse in the Aboriginal population [38]. Home(opathic) remedies and rat root are preferred by Native/Aboriginal students, who turn to Elders to learn about NHP [24].…”
Section: Resultsmentioning
confidence: 99%
“…However, some difficulty has been reported in implementing these policy initiatives, with some First Nations feeling that non-Aboriginal governments do not have the right to dictate private behaviours, and therefore ordinary community members are unlikely to accept such regulations (Orisatoki 2013). However, some places within Canada have enforced certain legislation, including Smoke-Free Ontario in 2006, which prohibited smoking in workplaces, enclosed public spaces, and motor vehicles when a minor under the age of 16 is present; banned the public display of tobacco products; and prohibited youth-targeted products such as flavoured cigarillos (Ontario Ministry of Health and LongTerm Care 2011).…”
Section: Major Policy Developments Among Countriesmentioning
confidence: 99%
“…The research base from this review has demonstrated that early collaboration and engagement with Indigenous community members is imperative to successful implementation of initiatives and programs within communities (Carson et al 2012a;Sibthorpe et al 2002). Indeed, a review of tobacco use and misuse among Aboriginals in Canada identified that health professionals play a critical role in reducing tobacco use through health intervention programs (Orisatoki 2013). For Aboriginal health professionals in particular, the likelihood of engagement with Aboriginal patients is increased compared to non-Aboriginal health professionals.…”
Section: Training Health Professionals In Smoking Cessation and Tobacmentioning
confidence: 99%
See 1 more Smart Citation